Impacts of edge effects on the invasion of alien plant species in Bantimurung Bulusaraung National Park, Indonesia - WARDIMAN MAS'UD; RISMA ILLA MAULANY; PUTU SUPADMA PUTRA; PUTU OKA NGAKAN (Society for Indonesian Biodiversity, 2023)
Abstract. Mas’ud W, Maulany RI, Putra PS, Ngakan PO. 2023. Impacts of edge effects on the invasion of alien plant species in Bantimurung Bulusaraung National Park, Indonesia. Biodiversitas 24: 6160-6168. Invasive Alien Plant Species (IAPS) are a threat to biodiversity and natural ecosystems. Factors influencing the IAPS distribution are well-known, but the impact of edge effects on the distribution is rarely discussed. This study aims to reveal the effect of differences in physical environmental factors along the edge effect gradient on the distribution of IAPS in Bantimurung Bulusaraung National Park, South Sulawesi, Indonesia. Twenty-five line transects were established where 125 plots (20m x 20m) were systematically located to analyze the density, dominance, and distribution of IAPS on the edge bordering natural forest ecosystems and anthropogenically disturbed areas. Of the 21 IAPS found, 95.2% were distributed in clumps and 4.8% at random. As the light intensity decreases significantly (r = 0.042; p = 0.029) with the increasing distance from the edge to the forest interior, the IAPS density decreases significantly (r = -0.512; p = 0.0001). Species of IAPS that experienced a decrease in individuals were those with a habitus of herbs and shrubs. Considering that the seedlings were found to spread outside their mother tree stands, Swietenia macrophylla King. and Maesopsis eminii Engl. are suspected to be long-lived IAPS that have the potential to spread to natural karst forest ecosystems, so they need to be monitored continuously.